Selected Writings: George Herbert Mead 1863-1931 - George Herbert Mead; Andrew J. Reck (Chicago: The University of Chicago Press, 1981)
George Herbert Mead (1863-1931) was, after John Dewey, America's most creative pragmatist philosopher in the period between World War I and the Great Depression. This volume furnishes a selective collection of those writings which he himself published during his lifetime.
(NP(B/12509s
Keywords: the social self; a pragmatic theory of truth; scientific method